Automotive Engineering Drawing Learning: Effective Online Learning Using Autocad Application - Mutohhari, Farid; Sudira, Putu; Nurtanto, Muhammad (Universitas Pendidikan Ganesha, 2021)
Learning outcomes are not satisfactory and student learning motivation is low. As a result, students cannot fully master the competency of automotive engineering drawings which are learning outcomes.. This study aims to analyze the effect of using autocad software to improve students' online learning outcomes of automotive engineering drawings. This quasi-experimental study used a pretest-posttest design and a control group. All class X students of the engineering and motorcycle business expertise program in two vocational schools became the population in this study. The sample used in this study amounted to 112 students who were divided into 4 classes in two vocational schools. The data collection technique was carried out using tests with multiple choice objective test instruments and drawing worksheets. The collected data were analyzed using descriptive statistics and inferential statistics with t test. The results of the t test obtained tcount = 9.703 with ttable at a significance level of 5% = 1.986. These results show the value of tcount> ttable, so that it accepts Ha and rejects H0. Thus it is concluded that the use of autocad software in online learning automotive engineering drawings has a significant effect on improving student online learning outcomes.